The Engrailed-1 Gene Stimulates Brown Adipogenesis - Chuanhai Zhang; Yibing Weng; Fangxiong Shi; Wanzhu Jin (Stem Cells International)
As a thermogenic organ, brown adipose tissue (BAT) has received a great attention in treating obesity and related diseases. It has been reported that brown adipocyte was derived from engrailed-1 (EN1) positive central dermomyotome. However, functions of EN1 in brown adipogenesis are largely unknown. Here we demonstrated that EN1 overexpression increased while EN1 knockdown decreased lipid accumulation and the expressions of key adipogenic genes including PPARγ2 and C/EBPα and mitochondrial OXPHOS as well as BAT specific marker UCP1. Taken together, our findings clearly indicate that EN1 is a positive regulator of brown adipogenesis.